The Influence of School Facilities and E-Learning on The Performance of State Junior High School Teachers - Yulista, Helda; Nugroho, Herry Setiyo; Widayatsih, Tri (Journal of Social Work and Science Education, 2023)
This study aims to identify and describe the facilities school and learning e-learning online together- same Against Performance Teacher Junior High School Country Subdistrict Kayuagung. This research is quantitative. Data collection tool using a questionnaire. Data analysis techniques used descriptive analysis tests, t tests, F tests and estimation tests using SPSS 22.00. The results of the analysis state that (1) there is a significant influence between school facilities on the performance of state junior high school teachers in the Kayuagung District; (2) There is a significant influence between e-learning on the performance of state junior high school teachers in the Kayuagung District; (2) There is a jointly significant influence between school facilities and e-learning on the performance of State Junior High School teachers in the Kayuagung District with a large influence of school facilities and e-learning on the performance of State Junior High School teachers in the Kayuagung District together. equal to 97.4% and the remaining 2.6% is influenced by other factors not examined in this study.